Quantification and modelling of water flow in rain-fed paddy fields in NE Thailand: evidence of soil salinization under submerged conditions by artesian groundwater - Hammecker, C.; Maeght, J.L.; Grunberger, O.; Siltacho, S.; Srisruk, K.; Noble, A.D. (Elsevier, 2012)
Water flow and solute transport in soils forms an essential part in many groundwater hydrology studies. This is especially true for Northeast Thailand, where the agricultural land is affected by the soil salinity, which is a widespread and an increasing phenomenon affecting 25% of the agricultural land. Salinization appears as scattered discrete patches of 10-100 m2 in the lowlands, illustrated by white efflorescences during the dry season and bare soil during the cropping season. A field study was undertaken in farm plots to measure the water flow and solute transport within the soil surface and the vadose zone, both inside and outside a saline patch. The water flow was measured on the soil surface with lysimeters and infiltration rings, and was derived in the soil from the hydraulic gradients measured with tensiometers placed at different depths. The salt transport was evaluated with water traps also placed at different depths, where the soil water's electrical conductivity was measured throughout the rainy season. Field study results demonstrated that the accumulation of saline solutions in rain fed paddy fields, occurred mainly during the rainy season while the soil surface remained flooded. During this period the saline water table rose towards the soil surface independently of infiltration into the soil. It happened in specific places where the compacted soil layer, generally ubiquitous in the area at a depth of 40-50 cm, is interrupted. Therefore salinity appeareds in discret points as patches. Artesian upward flow already described in this area (Haworth et al., 1966; Williamson et al., 1989; Imaizumi et al., 2002) is most probably responsible for this water table rise, thereby affecting crop productivity. Numerical modelling of water flow using HYDRUS-3D further supported these results and showed that managing the depth of flooding within the plot can significantly reduce the outbreak of these saline plumes.